Protective and pathological roles of regulatory immune cells in human cytomegalovirus infection following hematopoietic stem cell transplantation. (16th December 2021) - Namdari, Haideh; Hosseini, Maryam; Yazdanifar, Mahboubeh; Farajifard, Hamid; Parvizpour, Farzad; Karamigolbaghi, Maryam; Hamidieh, Amir Ali; Rezaei, Farhad
Abstract: Human cytomegalovirus (HCMV) is ubiquitously prevalent. Immune system in healthy individuals is capable of controlling HCMV infection; however, HCMV can be life‐threatening for immunocompromised individuals, such as transplant recipients. Both innate and adaptive immune systems are critically involved in the HCMV infection. Recent studies have indicated that regulatory immune cells which play essential roles in maintaining a healthy immune environment are closely related to immune response in HCMV infection. However, the exact role of regulatory immune cells in immune regulation and homoeostasis during the battle between HCMV and host still requires further research. In this review, we highlight the protective and pathological roles of regulatory immune cells in HCMV infection following hematopoietic stem cell transplantation (HSCT).